The influence of individuals in the shaping of Australian Antarctic policy 1900-1991 - Manning, John (2017)
In the nineteenth century knowledge of Antarctica was gained through the reports of whalers and scientific expeditions. Their reports of a hostile environment and limited economic potential did nothing to attract the involvement of colonial governments. At the start of the twentieth century a connection was fostered by British sponsored expeditions which called at Australian ports en route to Antarctica and sought personnel and financial support. Several Australian scientific adventurers joined these expeditions, but although greater awareness of Antarctica was gained, especially through the deeds of Douglas Mawson, Phillip Law and Richard Casey, Antarctica remained a territory of minor interest to Australian governments. This thesis seeks to explain how Antarctica, generally accorded very low priority in the estimation of government, could at times occupy the attention of Ministers, occasionally of the Prime Minister. It is argued that in the absence of economic interest explanation requires recognition of the role of highly motivated individuals for whom Antarctica became a ruling obsession in their lives. This study, while not downplaying the occasional role of international political concerns, focuses on the role of eight individuals, from diverse backgrounds, who it is argued played key roles in the development of Australian Antarctic policy in the twentieth century. It presents a fresh contribution to understanding the factors behind Antarctic policy from 1900 to 1991.